Pendampingan Gizi Spesifik dan Perilaku Ibu dalam Pola Asuh Anak Stunting Usia 6-24 Bulan - Simbolon, Demsa; Soi, Beatrix; Ludji, Ina Debora Ratu; Bakoil, Mareta Bakale (Jurnal Promosi Kesehatan Indonesia, 2022)
Background: From pregnancy, until the child is two years old, it is a prone period for stunting due to inadequate nutritional care at the family level. Mothers' ability in parenting and child health will affect their nutritional status and health, especially mothers who have stunted children. This study aimed to determine the effectiveness of specific nutrition assistance (SNA) through empowering cadres to change the behavior (knowledge, attitudes, practices) of mothers who have stunted children aged 6-24 months.Method: The research used a quasi-experiment with pre-post design with a control group. The research was conducted in Bengkulu Utara (BU) District and Timur Tengah Selatan (TTS) District. The intervention group received SNA for six months (June-November 2019) by Posyandu cadres and health workers. The control group received standard services from the Health Center or the Posyandu. Whilst, the intervention group received nutrition and health counseling during home visits. Mothers' knowledge, attitudes, and practices in parenting and child health nutrition were measured as dependent variables. Sample of 120 mothers with stunted children aged 6-24 months. Data analysis used independent t-test and dependent t-test.Results: The SNA was effective in increasing the knowledge, attitudes, and practices of mothers. The increased knowledge, attitudes, and practices were higher in the intervention group both in BU District (116%) and TTS District (26.33%). In BU District, there was an increase in knowledge (116%), attitude (40%), and practices (20.07%), likewise in TTS District; there was an increase in knowledge (26.33%), attitudes (42.5%), and practices (22.15%) which are significantly different from the increase in the practices of the control group. SNA needs to be carried out continuously to increase mothers' ability in parenting and child health. Therefore, that stunted children can catch up with their height growth.